Revitalisasi dan Konservasi Permukiman Tua Kota Balikpapan Sebagai Identitas Kota - Rilia Rigina Mahagarmitha (RUAS, 2022)
The development of a city can be influenced by several things, including the geographical location and the condition of the natural resources of the region or area, one example is the city of Balikpapan whose development was initiated by the presence of petroleum natural resources, so that until now the city of Balikpapan is still known as